DIGITAL-BASED PUBLIC SERVICE TRANSFORMATION THROUGH THE IMPLEMENTATION OF THE PROBOLINGGO PORTAL: A STUDY AT THE DEPARTMENT OF COMMUNICATION AND INFORMATICS OF PROBOLINGGO REGENCY - Hasan, Muhammad; Marwiyah, Siti; Maksin , Mastina (Jurnal PUBLIQUE, 2026)
This Digital transformation in public service delivery has become a strategic agenda in government reform, particularly through the adoption of information technology-based systems. This study aims to analyze the implementation of the Probolinggo Portal as a digital public service innovation in Probolinggo Regency, with a focus on the role of the Department of Communication and Informatics as the primary managing institution. A qualitative descriptive approach was employed to explore the implementation dynamics through in-depth interviews, observations, and documentation. The analysis was conducted using Edward III’s policy implementation framework, which includes communication, resources, implementers’ disposition, and bureaucratic structure. The findings indicate that the Probolinggo Portal has contributed to improving service efficiency, enhancing transparency, and expanding public access to government services. At the same time, several challenges remain, including limited communication effectiveness, uneven digital infrastructure, varying levels of digital literacy among citizens, and suboptimal inter-agency coordination. The interaction among implementation variables demonstrates a strong interdependence, where weaknesses in one dimension affect the overall effectiveness of the policy. The study highlights that successful digital public service implementation requires an integrative approach that goes beyond technological adoption, emphasizing organizational capacity building, adaptive communication strategies, and inclusive service accessibility for citizens.